Electroactivity across the cell wall of Gram-positive bacteria - Paquete, Catarina M. (2021)
Funding Information: This work was supported by national funds through FCT? Funda??o para a Ci?ncia e a Tecnologia, I.P. Project UIDB/04612/2020, UIDP/04612/2020 and PTDC/BIA-BQM/30176/2017, and by the European Union's Horizon 2020 research and innovation programme under grant agreement No 810856. Funding Information: This work was supported by national funds through FCT– Fundação para a Ciência e a Tecnologia, I.P., Project UIDB/04612/2020, UIDP/04612/2020 and PTDC/BIA-BQM/30176/2017, and by the European Union’s Horizon 2020 research and innovation programme under grant agreement No 810856. Publisher Copyright: © 2020 The Author(s) Copyright: Copyright 2021 Elsevier B.V., All rights reserved.